سانسورى رۆژنامەنووسى شێواز و جۆر و ئاڕاستەکانى - محمد, محمد دلێر امین (Sulaimani Journal for Humanities, 2003)
Censorship of the press has and history which goes back to the printing revolution during the fifteenth century in which it appeared in new styles . At any stage and under any political power , and in any society it obstructed the path of freedom of the press in different forms and styles. There have been many researches and studies about the press freedom , but only a few have been about 'Censoi sirip as an effective opponent against the freedom of thought and speech. As to the Kurdish Language, the history of journalism goes back to one hundred and five years ago. It also, suffered from the plague of 'Censorship right from the beginning. In this research , the types of Censorship have been shown and explained, among these : Censorship of authorization , Censorship of monitoring, Censorship of finance journalism , and self- Censorship as well Besides , the factors behind Censorship and its appearing among different regimes , As well as solutions and ways of combating those factors by journalists and the intellectual elite have been discussed. This research could be considered the first steep of tens of other academic studies and researches , to be written in Kurdish , that can be an attempt to widen the scope of freedom of the press .It may also be an encouragement to journalists to realize their own duties and rights , and to persist in their massage , which is truthfulness and protecting the public interest , for today and tomorrow as well. It is , also , an effort to let the journalists face the different faces of Censorship.